Jus Cogens A Critical Journal of Philosophy of Law and Politics - Corradetti, Claudio; Kumm, Mattias; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer.)
The journal promotes critical reflections on fundamental questions in the theory of law and politics. It welcomes studies widening the understanding of the practice of law and politics, providing orientation with regard to the possibilities of emancipatory change with particular attention to disadvantaged groups and gender discrimination. Cognizant of the role of domination in the practice of law and politics, the journal is open to cross-disciplinary studies assessing the role of the economic interests and ideology in maintaining and legitimizing power, as well as to critical or reconstructive normative reflections regarding its justification.
Keywords: Political theory; Political science; Law -- Philosophy; Law; International law; Sources and Subjects of International Law, International Organizations; Theories of Law, Philosophy of Law, Legal History; Philosophy of Law; Political Theory